Bridging east and west: integrative approaches to obesity management through traditional Chinese medicine - Li, Qianrong; Liu, Zhao; Zhang, Xiaolin (Frontiers in Endocrinology, 2025)
This study provides a comprehensive review of research pertaining to the treatment of obesity using traditional Chinese medicine (TCM). It encompasses fundamental theories, epidemiological data, pathological mechanisms, clinical practices, technological advancements, and directions for future research. In the section on fundamental theories, the etiology, pathogenesis, historical development, and theoretical foundations of obesity within TCM are examined. The current state of obesity has been analyzed through an epidemiological lens, along with the application of TCM and relevant clinical research findings. The pathological mechanism section evaluates the effect of TCM on metabolic regulation, inflammatory responses, and adipocyte functionality in the context of obesity. Clinical practices are illustrated through case studies of commonly utilized TCM prescriptions, acupuncture, moxibustion therapy, and integrative approaches combining traditional Chinese and Western medicine. The Technological Advancements section discusses the emergence of new formulations, modern diagnostic technologies, and personalized treatment strategies. The future outlook addresses potential research trajectories, prospects for integrating TCM with contemporary medical practices, and trends in international collaborations. Evidence suggests that TCM holds promise in various aspects of obesity treatment. However, further investigation is necessary to elucidate its efficacy and underlying mechanisms, enhance international cooperation and standardization efforts, and foster the advancement of TCM in obesity management.